PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, DAN LOKASI TERHADAP KEPUASAAN KONSUMEN CAFÉ KOPI SUSU BAPER DI KOTA METRO - Andriyan Apriyono; Ktut Murniati; Maya Riantini (Universitas Galuh, 2022)
The increase in coffee consumption makes coffee shops more widespread, the intense competition between coffee shops makes coffee shop entrepreneurs have to continue to innovate and pay attention to consumer satisfaction. This study aims to analyze consumer evaluation of product quality, service quality, and level of customer satisfaction, also the effect of product quality, service quality, and location on consumer satisfaction. This study used a survey method. The sampling technique in this study used the purposive sampling method. The sample collection method used accidental sampling, which means that all consumers who have ever purchased products at Café Kopi Susu Baper. The number of samples in this study was 45 people. The research location was determined deliberately at Café Kopi Susu Baper because Café Kopi Susu Baper was one of the cafes in Metro City with private property rights and has been in existence for two years. Data collection from February to March 2021. Data analysis used qualitative descriptive analysis and multiple linear regression. The result showed that the product quality variable was included in the high category with an index value of 187,66. The service quality variable was included in the high category with an index value of 191,98. The consumer satisfaction variable was in the high category with an index value of 200,67. Product quality, service quality, and location variables have a positive and significant effect on customer satisfaction. Based on the coefficient of partial determination shows that service quality was a variable that has a dominant influence on customer satisfaction.